Integrated assessment of the cybersecurity level of critical infrastructure in a post-quantum environment - Melenti, Yevhen; Murr, Pierre; Aksonova, Iryna; Bukatych, Illia; Sitchenko, Oleksandr (Національний технічний університет "Харківський політехнічний інститут", 2025)
The relevance of the study is due to the increasing complexity of cyber threats in the post-quantum environment, the development of quantum computing technologies and the intellectualization of data management and processing processes. In the context of the spread of hybrid and synergistic attacks combined with social engineering methods, traditional approaches to assessing the security of critical infrastructure objects (CIF) are becoming ineffective. This requires the implementation of an integrated methodology for assessing the level of cyber security, capable of adaptively reflecting the real state of security and taking into account the impact of post-quantum threats. The subject of the study is the process of integrated assessment of the level of cyber security of CIF in the post-quantum environment using mathematical and analytical methods. The purpose of the article is to develop a methodology for integrated assessment of the level of security of CIF in the post-quantum environment taking into account modern hybrid and synergistic cyber threats. Results obtained. A methodology for assessing the level of security based on a synergistic threat model is proposed, which takes into account the categories of attackers, their goals, resources and capabilities. A mathematical formalization of a unified classifier of cyber threats has been developed, which forms tuples taking into account the features of hybridity, synergy, and social engineering factors. A mathematical apparatus has been formed for modeling the implementation of cyber threats and determining the level of resilience of CIF cyber systems in a post-quantum environment. Conclusions. Assessment of CIFsecurity makes it possible to identify critically important information assets, assess the effectiveness of protection measures, and identify vulnerable elements. The results of the study confirm the feasibility of implementing intelligent multi-circuit protection systems based on post-quantum algorithms to ensure the appropriate level of cyber resilience in a post-quantum environment.

Актуальність дослідження зумовлена зростанням складності кіберзагроз у постквантовому середовищі, розвитком квантових обчислювальних технологій та інтелектуалізацією процесів управління й оброблення даних. В умовах поширення гібридних і синергетичних атак, що поєднуються з методами соціальної інженерії, традиційні підходи до оцінювання безпеки об’єктів критичної інфраструктури (ОКІ) стають малоефективними. Це потребує впровадження інтегрованої методики оцінки рівня кіберзахищеності, здатної адаптивно відображати реальний стан безпеки та враховувати вплив постквантових загроз. Предметом дослідження є процес інтегрованої оцінки рівня кіберзахищеності ОКІ в постквантовому середовищі з використанням математичних та аналітичних методів. Метою статті є розроблення методики інтегрованої оцінки рівня захищеності ОКІ в постквантовому середовищі з урахуванням сучасних гібридних та синергетичних кіберзагроз. Отримані результати. Запропоновано методику оцінювання рівня захищеності на основі синергетичної моделі загроз, що враховує категорії зловмисників, їх цілі, ресурси та можливості. Розроблено математичну формалізацію уніфікованого класифікатора кіберзагроз, який формує кортежі з урахуванням ознак гібридності, синергізму та соціоінженерних факторів. Сформовано математичний апарат для моделювання реалізації кіберзагроз і визначення рівня стійкості кіберсистем ОКІ в постквантовому середовищі. Висновки. Оцінка захищеності ОКІ дає змогу визначити критично важливі інформаційні активи, оцінити ефективність засобів захисту та виявити вразливі елементи. Результати дослідження підтверджують доцільність упровадження інтелектуальних багатоконтурних систем захисту на основі постквантових алгоритмів для забезпечення належного рівня кіберстійкості в постквантовому середовищі.
Інтегрована оцінка рівня кіберзахищеності критичної інфраструктури в постквантовому середовищі
Keywords: post-quantum threats; synergistic cyber threat model; integrated safety indicator; critical infrastructure facility; intelligent multi-circuit protection system; постквантові загрози; синергетична модель кіберзагроз; інтегрований показник безпеки; об'єкт критичної інфраструктури; інтелектуальна багатоконтурна система захисту